An In Vitro Evaluation of Alumina, Zirconia, and Lithium Disilicate Surface Roughness Caused by Two Scaling Instruments. Issue 2 (18th December 2015) - Vigolo, Paolo; Buzzo, Ottavia; Buzzo, Maurizio; Mutinelli, Sabrina
Abstract: Purpose: Plaque control is crucial for the prevention of inflammatory periodontal disease. Hand scaling instruments have been shown to be efficient for the removal of plaque; however, routine periodontal prophylactic procedures may modify the surface profile of restorative materials. The purpose of this study was to assess in vitro the changes in roughness of alumina, zirconia, and lithium disilicate surfaces treated by two hand scaling instruments. Materials and Methods: Forty‐eight alumina specimens, 48 zirconia specimens, and 48 lithium disilicate specimens, were selected. All specimens were divided into three groups of 16 each; one group for each material was considered the control group and no scaling procedures were performed; the second group of each material was exposed to scaling with steel curettes simulating standard clinical conditions; the third group of each material was exposed to scaling with titanium curettes. After scaling, the surface roughness of the specimens was evaluated with a profilometer. First, a statistical test was carried out to evaluate the difference in surface roughness before the scaling procedure of the three materials was effected (Kruskal‐Wallis test). Subsequently, the effect of curette material (steel and titanium) on roughness difference and roughness ratio was analyzed throughout the entire sample and within each material group, and a nonparametric test for dependent values was conducted (Wilcoxon signed‐rank test). Finally, the roughness ratios of the three material groups were compared by means of a Kruskal‐Wallis test and a Wilcoxon signed‐rank test. Upon completion of profilometric evaluation, representative specimens from each group were prepared for SEM evaluation to evaluate the effects of the two scaling systems on the different surfaces qualitatively. Results: After scaling procedure, the roughness profile value increased in all disks. Classifying the full sample according to curette used, the roughness of the disks treated with a steel curette reached a higher median value than that of the titanium group. Zirconia demonstrated the least significant increase in surface roughness. The result was 3.9 times of the initial value as compared to 4.3 times for alumina and 4.6 times for lithium disilicate. Conclusions: Comparison of profilometer readings before and after instrumentation, carried out with different hand scaling instruments, highlighted both a statistically and clinically relevant increase in material roughness.